Probiotic, a tool in livestock and aquaculture production - López-Acevedo, Edgar (2013)
The probiotics are products based on different microorganism strains, those products have evolved from a just simple mixture of active bacteria to products with specific properties of adherence, colonization, synergies, antibacterial activity, etc. Probiotic products for livestock and aquaculture production are designed with strains developed to operate under specific conditions and which need to be understood and taken into account by the producers because different results can be observed depending of specie(s), geographic area, and type of culture production. The available information suggests that probiotic display a progress from: (a) a better understanding of the bacterial micro-ecosystem and target organs, (b) strain source and their particular characteristics, (c) doses and target species, (d) specific adhesion and/or colonization mechanisms, (e) specific activation of the immune system, and, (f) environmental effects. The aim of this manuscript is to provide information to the livestock and aquaculture producers about the characteristics and qualities of probiotic so they can carry out a proper selection and use.